2010
DOI: 10.1002/ejoc.200901520
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Heterocycles by Intramolecular Nucleophilic Substitution at an Electron‐Deficient sp2 Nitrogen Atom

Abstract: Abstract2‐Aryl(arylsulfonyl)‐6,7‐dihydro‐2H‐imidazo[2,1‐c][1,2,4]triazol‐3(5H)‐ones and 3‐arylimino‐6,7‐dihydroimidazo[2,1‐c][1,2,4]thiadiazoles have been synthesized by intramolecular nucleophilic substitution reactions at the electron‐deficient sp2 nitrogen atom of 2‐(hydroxyimino)imidazolidine O‐sulfonate. The displacement of the sulfate leaving group by both nitrogen and sulfur anionic nucleophiles proceeds exothermically by in‐plane SN2σ nucleophilic substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…7 Therefore, the nucleophilic addition products 2a-d were treated with a strong base to form the ambident carboximidate anions D, which, we expected, would undergo intramolecular electrophilic amination [12][13][14] with simultaneous extrusion of methoxide or benzyloxide anion (Scheme 3). However, we found that treatment of 2a-d with bases such as sodium hydroxide, triethylamine or pyrrolidine did not provide the desired imidazo[2,1-c][1,2,4]triazol-3-ones (E), which indicated that the anions D are rather weak nucleophiles, unable to induce the intramolecular electrophilic amination reactions at the sp 2 -hybridized nitrogen atom of the exocyclic alkoxyimino group.…”
Section: Resultsmentioning
confidence: 99%
“…7 Therefore, the nucleophilic addition products 2a-d were treated with a strong base to form the ambident carboximidate anions D, which, we expected, would undergo intramolecular electrophilic amination [12][13][14] with simultaneous extrusion of methoxide or benzyloxide anion (Scheme 3). However, we found that treatment of 2a-d with bases such as sodium hydroxide, triethylamine or pyrrolidine did not provide the desired imidazo[2,1-c][1,2,4]triazol-3-ones (E), which indicated that the anions D are rather weak nucleophiles, unable to induce the intramolecular electrophilic amination reactions at the sp 2 -hybridized nitrogen atom of the exocyclic alkoxyimino group.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, at room temperature compound D undergoes a reaction with three molar equivalents of phenyl isothiocyanate that, following desulfurization, affords 3-phenyl-2-phenylimino-2,6,7,8-tetrahydroimidazo[1,2-a] [1,3,5]triazine-4(3H)-thione (20) as the sole product [31]. However, a tandem nucleophilic addition-electrophilic amination reaction takes place when D is treated with aryl isothiocyanates at 40°C; 6,7-dihydro-5H-imidazo[2,1-c] [1,2,4]thiadiazole (21) is formed in case of 4-methylphenyl isothiocyanate, and 7-substituted derivatives 22 and 23 are obtained in the case of more reactive phenyl and p-chlorophenyl isocyanates [35].…”
Section: Reactions With Heterocumulenesmentioning
confidence: 97%
“…oxaziridine derivatives: rise to the formation of heteroaromatic hydroxylamine-O-sulfonates E, which in solid state and in solution exist in the form of betaines [34,35]. Importantly, the competitive N-amination reaction of a heterocyclic ring has not been perceived.…”
Section: Synthesis Of Heterocyclic Hydroxylamine-o-sulfonatesmentioning
confidence: 97%
See 2 more Smart Citations